Better Students Ask More Questions.
Roger is 6 years older than Zoe.Three years ago,Zoe's age was two-thirds of Roger's...
1 Answer | add yours
(Level 1) Associate Educator, Expert
Let x be the age of Roger.
Let y be the age of Zoe.
We know that AT PRESENT, x = y + 6.
Three years ago, the age of Roger is x - 3. The age of Zoe is y - 3.
We know that THREE YEARS AGO, `y - 3 = 2/3 (x- 3).`
Now, we have two equations. The first equation is the relationship of their ages at present: x - y = 6. While the second equation is the relationship of their ages three years ago (which simplifies to): -2x + 3y = 3.
Let us use substitution. Isolating x from the first equation, we get x = 6 + y. We then substitute this to the second equation:
`-2x + 3y = 3 rArr -2(y+6) + 3y = 3 rArr -2y - 12 + 3y = 3 rArr y - 12 = 3 rArr y = 15.`
This implies that x = 21 (since x - 15 = 6).
Therefore, at present, Roger is 21 years old and Zoe is 15 years old.
[To check: three years ago, Roger was 18, Zoe 12; and 12 is 2/3 of 18. Hence, the answer is correct]
Posted by mvcdc on May 11, 2013 at 1:50 PM (Answer #1)
Join to answer this question
Join a community of thousands of dedicated teachers and students.